Development of Lesson Plan (LP) with Software Lectora Inspire Assisted Problem-Based Learning in Improving Learning Outcomes for Senior High School - Achmad Aswal; Hunaidah Hunaidah; Erniwati Erniwati (Indonesian Review of Physics (IRiP), 2022)
This research-based on technological advances that promote the use of technology in learning, on the lack of valid, practical and effective lesson plans, particularly in problem-based learning models that are in line with the 2013 curriculum, and on the use of Lectora Inspire Software in the creation of lesson plans. This study was conducted to develop a product that is a problem-based learning model based on Lectora Inspire software, and that is valid, practical and effective. This type of research is research and development (research and development). The design of this study based on 5 out of 10 phases of Borg and Gall's research design, namely research and collection of initial information, planning, development of original product formats, initial testing and product improvement. The effectiveness test results were rated as very good if the results of the analysis of the responses of teachers and students with an average of 88% and 89.04% as and the increase (n-gain) of student learning outcomes is 0.62 which can be categorized as a moderate increase.